Calculating Launch Windows for Transfers of Solar Powered EP Spacecraft between Low-earth Non-coplanar Circular Orbits. (2017) - Ishkov, S.A.; Petrukhina, K.V.; Salmin, V.V.
Abstract: The paper considers the problem of finding such conditions for launch of a low thrust electric propulsion (EP) spacecraft from circular low orbit that the passage through Earth shadow along the transfer trajectory would be minimized. An approximate method of calculating shadow intervals on the loops of a near circular oscillating orbit is suggested. A precise method, based on numerical integration of the equations of motion and calculation of Sun's ephemerides is developed. A series of trajectories for transfers to geostationary orbit (GEO) were computed for various launch dates and longitudes of ascending node. Based on the calculations, isolines of aggregate shadow time were built. They allow an optimal launch date and initial position of ascending node.